Separating the sex from the object: conceptualizing sexualization and (sexual) objectification in Flemish preteens' popular television programs. Issue 3 (3rd July 2018) - Rousseau, Ann; Eggermont, Steven; Bels, Annebeth; Van den Bulck, Hilde
Abstract: Media effects research has confirmed that sexualizing media exposure can negatively affect preteens' body image and sexual development. While there is a link between sexualizing content and adverse outcomes such as self-objectification and body dissatisfaction, an interest in sexual media content is a normal part of healthy sexual development during the preteen years. Hence, research is needed that examines the variety in preteens' sexual media diet thereby addressing the subtleties involved in sexualizing media. To what extent do sexual content, appearance-related content, sexual objectification, and objectification occur in Flemish preteens' favorite TV shows? And, how are these different types of content related to gender roles? Seeking to address these questions, this article reports on a quantitative content analysis of 24 episodes from five TV shows popular among Flemish preteens. Drawing on a sample of 465 scenes, results demonstrated that one in five scenes contained sexual behavior, and one in ten contained sexual objectification. Male characters were sexually objectified as often as female characters. Women were more often judged for their appearance, but were also more often shown treating others as objects in a non-sexual way. Results are discussed in light of objectification and social cognitive theory, culminating in suggestions for future research and implications for parents.